Dynamic correlations between microbiota succession and flavor development involved in the ripening of Kazak artisanal cheese. (March 2018) - Zheng, Xiaoji; Liu, Fei; Shi, Xuewei; Wang, Bin; Li, Kaixiong; Li, Baokun; Zhuge, Bin
Abstract: Cheese is a typical handcrafted fermented food in Kazak minority from the Uighur Autonomy Region in China. The ripening process of the cheese is crucial for quality and flavor. The aim of this study was to gain a deeper knowledge on the bacterial and fungal community diversity at different time points during the post-ripening of the cheese and to understand the relationship between bacterial and fungal profiles and the chemical components including amino acids, fatty acids and volatile compounds related the cheese flavor. Cheese samples were collected from days 5, 10, 15, 20 and 30 after the starting point of post-ripening. The bacterial and fungal compositions were analyzed with next generation sequencing targeting the 16S rDNA loci for bacteria and ITS loci for fungi. The amino acids contents were analyzed by reversed phase high performance liquid chromatography combined with UV detection. The fatty acids and the volatile components were analyzed by Solid Phase Micro Extraction followed by Gas Chromatography/Mass spectrometry. We found that Lactobacillus, Streptococcus, Kluyveromyces and Torulaspora were the dominant cheese's population. Bidirectional orthogonal partial least squares (O2PLS) based correlation analysis between microbiota succession and flavor dynamics showed that bacteria made more contributions to flavor formation than fungi. Eight bacteria genera and seven fungi genera were determined as functional core microbiota for the flavor production based on their dominance and functionality in microbial community. This study provided a comprehensive picture of the dynamic changes of microbiota profiles through the post-ripening process. The elucidation of the causal relationship between microbiota and the flavor components has advanced our understanding of the mechanism underlying the cheese development. Graphical abstract: Highlights: Four genera dominated the ripening of Kazak artisanal cheese. The volatiles were strongly associated with the microbiota in Kazak artisanal cheese. Functional core microbiota was identified in Kazak artisanal cheese. Bacterial community made more contribution to flavor development than fungi.